Outcome of One Stage Urethroplasty Using Buccal Mucosa for Long Segment Urethral Stricture (Bangladesh Journal of Urology, 2020)
Objective: To assess the outcome of one stage urethroplasty using buccal mucosa for long segment (>2cm) urethral stricture.Material & Method: This retrospective study was done in a private Hospital at Jessore from May, 2010 to October, 2012. Twenty nine patients were managed with one stage dorsal on lay buccal mucosal graft (BMG). Patients were followed up 3 monthly with history, physical examination and relevant investigations. The mean duration of follow up was 23 months.Result: The age of the patients ranged from18 years to 65 years with mean of 35years. The length of the stricture ranged from 2.5cm to 10 cm with mean length 5.5 cm. The mean duration operative period was 3.5 hours with range from 2 hours to 4.5 hours. Of the 29 patients, 15 patients (51.7%) had bulbar urethral stricture, 10 patients (34.5%) had penile urethral stricture and 4 patients (13.8) had pan urethralstricture. Success was defined as normal voiding without further procedure. The rate of recurrence noted in this study was 10.34%.Conclusion: One stage dorsal on lay BMG urethroplsaty is a reliable and satisfactory procedure for the management of long segment urethral stricture with minimum complication.Bangladesh Journal of Urology, Vol. 18, No. 2, July 2015 p.68-73